Study on bioactivities of Morinda citrifolia L. fruit hydroalcoholic extracts and detection of novel phytoconstituents by UPLC-Q-exactive orbitrap-tandem mass spectrum analysis - Aslee Tailulu; Hanyue Cui; Liren Wu; Yuhu Shen; Ping Shi (Exploration of Drug Science)
Aim: The objective of this study is to ascertain the antimicrobial and anticancer properties of dry Morinda citrifolia L. (noni) pulp hydroalcoholic extracts. Methods: In this study, dry noni samples were immersed in hydro-alcoholic solvents, ethanol (EtOH) and methanol (MeOH). Using the intelligent-flash extractor (KBE-I5) and freeze-vacuum dryer, noni ethanol (NE) and noni methanol (NM) extracts were obtained for antimicrobial testing against bacterial and fungal strains via disc diffusion assay. Cell viability was assessed using the cell counting kit-8 (CCK-8) assay, acridine orange (AO) staining, and western blotting to evaluate anticancer effects on human cancer cells. Novel phytoconstituents were identified using dual-mode ultra-performance liquid chromatography quadrupole exactive orbitrap-tandem mass spectrometer (UPLC-Q-exactive orbitrap-MS/MS) analysis. Results: Extraction yielded 16.8% for NE and 25.8% for NM. NE minimum inhibitory concentrations (MICs) against Escherichia coli (EC), Saccharomyces cerevisiae (SC), Staphylococcus aureus (SA), and Streptococcus thermophilus (ST) being 177, 52, 388, and 283 mg/mL. NM MICs values were 105, 47, 312, and 135 mg/mL, respectively. Anticancer half inhibitory concentrations (IC50s) for NE against human colon adenocarcinoma cell (HT-29) and human bladder cancer cell lines (UMUC-3) were 758 and 899 µg/mL. For NM, IC50s were 1,231 (HT-29) and 1,173 (UMUC-3) µg/mL. Cell death indicators include organelle deformities, AO fluorescence, and autophagy protein expression. In dual ion-scan mode UPLC analysis, 17 distinct phytoconstituents were identified, including 2-Hydroxycinnamic acid, 4-Hydroxycinnamic acid, and riboflavin, known for treating cancer, metabolic dysfunctions, and COVID-19. The 14 constituents were discovered in noni fruit for the first time. Conclusions: Noni fruit extracts show antimicrobial/anticancer activity and therapeutic potential, establishing noni fruit as a promising food and medicinal source based on composition.